Experimental investigation of friction coefficient of laboratory ice - Fransson, Lennart; Patil, Aniket; Andrén, Henrik (Luleå tekniska universitet, Byggkonstruktion och -produktion, 2011)
Friction processes of rubber on ice, steel on ice and ice on ice have been investigated bymeasuring contact forces in controlled laboratory experiments. A carefully prepared ice platewas rotated at a constant speed and brought into contact with a ring on which torque andnormal load was measured. Replicas of the different types of standardized ice surfaces werestudied in microscope. Friction of rubber on ice reached a maximum value at a sliding speedof abt. 100 mm/min. At a temperature of -10°C this maximum friction coefficient decreasedwith increasing ice surface roughness. Friction of steel on ice increased with decreasing speedand no maximum value was obtained. Ice sliding on ice at low speed resulted in high frictionforces when sintering took place. Godkänd; 2011; 20121116 (ysko)